2017
DOI: 10.1016/j.jaip.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Inpatient Beta-Lactam Allergies: A Multihospital Implementation

Abstract: Addressing inaccurate penicillin allergies is encouraged as part of antibiotic stewardship in the inpatient setting. However, implementing interventions targeted at the 10–15% of inpatients reporting a prior penicillin allergy can pose substantial logistic challenges. We implemented a computerized guideline for patients with reported beta-lactam allergy at five hospitals within a single healthcare system in the Boston area. In this paper, we describe our implementation roadmap, including both successes achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
111
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 54 publications
(62 reference statements)
1
111
0
3
Order By: Relevance
“…This approach is dependent on a collaborative working model that is led by an allergist with input from acute care physicians/infectious diseases specialists, nurses, pharmacists and hospital management. Blumenthal et al recently described their experience with this model, its evolution and the systematic approach involved in its implementation including overcoming barriers in a US healthcare framework. The limitations of their study are as follows: relatively small sample size and comparison of the 3 approaches that occurred over different time periods, retrospective data collection, they did not report on the categorization of patients with respect to previous history of immediate and non‐immediate HSR and follow‐up data regarding non‐immediate HS reactions following discharge from hospital. …”
Section: Approach 2: a Computerized Clinical Decision Support System mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is dependent on a collaborative working model that is led by an allergist with input from acute care physicians/infectious diseases specialists, nurses, pharmacists and hospital management. Blumenthal et al recently described their experience with this model, its evolution and the systematic approach involved in its implementation including overcoming barriers in a US healthcare framework. The limitations of their study are as follows: relatively small sample size and comparison of the 3 approaches that occurred over different time periods, retrospective data collection, they did not report on the categorization of patients with respect to previous history of immediate and non‐immediate HSR and follow‐up data regarding non‐immediate HS reactions following discharge from hospital. …”
Section: Approach 2: a Computerized Clinical Decision Support System mentioning
confidence: 99%
“…48 This approach is dependent on a collaborative working model that is led by an allergist with input from acute care physicians/infectious diseases specialists, nurses, pharmacists and hospital management. Blumenthal et al 49 Whilst their approach enabled acute care physicians to administer penicillin or cephalosporin to "low-risk" patients carrying a label of PenA, the patients were not definitively "de-labelled" as none of following criteria were met in full:…”
Section: Clinical Decision Support System (Cdss) For De -Labe Llin G mentioning
confidence: 99%
“…Penicillins are the first‐line antibiotics for many common infections and sepsis . Six to 10% of the general population and 15–20% of hospital inpatients in the UK and USA carry a penicillin allergy (PenA) label, although emergent research shows that 90–95% of these labels are found to be incorrect following comprehensive allergy testing . Identification and removal of inaccurate and spurious PenA labels is referred to as delabelling.…”
Section: Introductionmentioning
confidence: 99%
“…The first stage of direct PenA delabelling involves a comprehensive, structured assessment of the clinical history to establish a level of certainty and likelihood of the reported allergy. Clinical algorithms adapted from expert opinion, published studies and guidelines, have been proposed to aid structured risk stratification by nonspecialists . Paper and computer‐based stratification tools have been developed and employed at various stages of the patient's journey by clinicians and pharmacists in hospitalised patients and for preoperative testing .…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been developed and reported in the literature to attempt to decrease the inappropriate labeling of BL allergies and subsequent avoidance of BL therapy including penicillin skin testing, decision support tools for patients with documented penicillin allergies, and pharmacist-driven BL allergy interviews. [9][10][11][12][13][14] In a recent study, patients who received skin testing per hospital protocol and who were subsequently treated after provider utilization of a computerized guideline application with clinical decision support were 5.7 and 1.8 times more likely to receive a penicillin or cephalosporin, respectively. 14 A pilot-study of a standardized BL allergy questionnaire used by pharmacists found that 63% of assessed patients had previously tolerated a BL antibiotic resulting in BL prescriptions for 87.5% of the 24 patients deemed eligible for BL therapy.…”
mentioning
confidence: 99%